(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this investigation was to study the effect of isolated and combined Swiss ball and kettle bell training on Back Strength of adolescent boys. To achieve the purpose of this study, the investigator selected sixty adolescent boys as participants in the age group of 13 to 18 years from Andaman and Nicobar Island. They were divided into four groups of fifteen subjects each. Group-I underwent Swiss ball training, group-II underwent kettle bell training, group-III underwent combined Swiss ball and kettle bell training and group-IV acted as control. The data collected from the four groups prior to and post experimentation on Back Strength was statistically analyzed to find out the significant difference if any, by applying the analysis of covariance (ANCOVA). Since four groups were involved, whenever the obtained ‘F’ ratio value was found to be significant for adjusted post-test means, the Scheffe’s test was applied as post hoc test to determine the paired mean differences, if any. Due to Swiss ball (STG =6.34%), kettle bell training (KTG) =14.88%) and combined Swiss ball and kettle bell training (SKTG = 10.64%) the adolescent boy’s Back Strength was improved greatly.